Circadian clock regulation of the glycogen synthase (gsn) gene by WCC is critical for rhythmic glycogen metabolism in Neurospora crassa - Baek, Mokryun; Virgilio, Stela [UNESP]; Lamb, Teresa M.; Ibarra, Oneida; Andrade, Juvana Moreira [UNESP]; Goncalves, Rodrigo Duarte [UNESP]; Dovzhenok, Andrey; Lim, Sookkyung; Bell-Pedersen, Deborah; Bertolini, Maria Celia [UNESP]; Hong, Christian I. (Natl Acad Sciences, 2019)
Circadian clocks generate rhythms in cellular functions, including metabolism, to align biological processes with the 24-hour environment. Disruption of this alignment by shift work alters glucose homeostasis. Glucose homeostasis depends on signaling and allosteric control; however, the molecular mechanisms linking the clock to glucose homeostasis remain largely unknown. We investigated the molecular links between the clock and glycogen metabolism, a conserved glucose homeostatic process, in Neurospora crassa. We find that glycogen synthase (gsn) mRNA, glycogen phosphorylase (gpn) mRNA, and glycogen levels, accumulate with a daily rhythm controlled by the circadian clock. Because the synthase and phosphorylase are critical to homeostasis, their roles in generating glycogen rhythms were investigated. We demonstrate that while gsn was necessary for glycogen production, constitutive gsn expression resulted in high and arrhythmic glycogen levels, and deletion of gpn abolished gsn mRNA rhythms and rhythmic glycogen accumulation. Furthermore, we show that gsn promoter activity is rhythmic and is directly controlled by core clock component white collar complex (WCC). We also discovered that WCC-regulated transcription factors, VOS-1 and CSP-1, modulate the phase and amplitude of rhythmic gsn mRNA, and these changes are similarly reflected in glycogen oscillations. Together, these data indicate the importance of clock-regulated gsn transcription over signaling or allosteric control of glycogen rhythms, a mechanism that is potentially conserved in mammals and critical to metabolic homeostasis.
Keywords: circadian rhythms; Neurospora crassa; glycogen metabolism; glycogen synthase; glycogen phosphorylase